(untitled) (Islas, 2025)
Introduction: This article addresses the culture–nature relationship, its links and counterpoints, from a philosophical perspective through the analysis of a selection of representative authors in philosophical thought. Methods: The historical-logical method was used to carry out the analysis, which facilitates a chronological order of the authors and concepts under study. Hermeneutics facilitated the interpretation of the authors and their works. Results: The main links of the culture–nature relationship are identified from the standpoint of philosophy, with emphasis on its contradictory character as a result of specific social practices arising from certain types of production relations, where the assimilation of cultural heritage in relation to nature emerges. A key counterpoint lies in the need to conduct the study from a comprehensive perspective. Conclusions: The origins of the opposition between culture and nature can be significantly traced back to the Sophists, but it is during the Modern era—and in line with the consolidation and individualization of the sciences—that their articulation and functioning gained greater relevance.